Pyrolysis of organic molecules with applications to health and environmental issues - Moldoveanu, Serban (Techniques and instrumentation in analytical chemistry, 2010)
Pyrolysis of Organic Molecules with Applications to Health and Environmental Issues, the 28th volume in the Techniques and Instrumentation in Analytical Chemistry series, gives a systematic and comprehensive description of pyrolysis of non-polymeric organic molecules. Pyrolysis is involved in many practical applications as well as in many common human activities, but harmful compounds can be generated in the process. The study of pyrolysis and of the formation of undesirable compounds as a result of pyrolytic processes is of considerable interest to chemists, chemical engineers, and toxicologists. Pyrolysis results for compounds not previously studied or reported. Updated information from a large body of results published on pyrolysis of individual compounds or classes of compounds. Information on mechanisms and kinetics of numerous pyrolytic processes. .